(untitled) (Eurasian Scientific Herald, 2025)
The intensive development of agricultural production currently requires the expansion of the use of chemical plant protection products against insect pests, which in turn leads to environmental pollution and irreparable losses in the biocenosis. Therefore, the development of fundamentally new plant protection products, characterized by safety in relation to the environment and high selectivity of action, becomes more and more relevant. The use of sex pheromones in integrated plant protection systems leads to the need to develop convenient synthesis schemes that make it possible to obtain pheromones of various pest species with good yield and high isomeric purity from the same initial compounds - synthons